2008
DOI: 10.1016/j.stem.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Mediates Self-Organization and Axis Formation in Embryoid Bodies

Abstract: Summary Embryonic stem cells form descendants of all three germ layers when differentiated as aggregates, termed embryoid bodies. In vivo, differentiation of cells depends on signals and morphogen gradients that provide instructive and positional cues, but do such gradients exist in embryoid bodies? We report here the establishment of anteroposterior polarity and the formation of a primitive streak-like region in the embryoid body, dependent on local activation of the Wnt pathway. In this region, cells undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
406
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(442 citation statements)
references
References 76 publications
27
406
5
4
Order By: Relevance
“…1) (Brons et al 2007;Tesar et al 2007). Instead of stimulating self-renewal, Wnt signaling effectively stimulated differentiation of mESCs after they have been primed either by growth at a high density (Otero et al 2004) or by initial commitment in EB assays (Lindsley et al 2006;ten Berge et al 2008). Similar to hESCs, EpiSCs responded to inhibiting GSK3 by differentiating .…”
Section: Effects Of Wnt Stimulation and Gsk3 Inhibition Depend On Thementioning
confidence: 99%
“…1) (Brons et al 2007;Tesar et al 2007). Instead of stimulating self-renewal, Wnt signaling effectively stimulated differentiation of mESCs after they have been primed either by growth at a high density (Otero et al 2004) or by initial commitment in EB assays (Lindsley et al 2006;ten Berge et al 2008). Similar to hESCs, EpiSCs responded to inhibiting GSK3 by differentiating .…”
Section: Effects Of Wnt Stimulation and Gsk3 Inhibition Depend On Thementioning
confidence: 99%
“…We have previously reported that CD146 induces the epithelial-mesenchymal transition by downregulating the expression of E-cadherin in breast cancer cell lines 16 . E-cadherin, an adhesion molecule anchoring b-catenin to the cell membrane, has been identified as a canonical Wnt target gene and is positively regulated by Wnt 41,42 . In this study, we demonstrate that CD146 is the negative regulator of canonical Wnt signalling.…”
mentioning
confidence: 99%
“…Wnt3a is added to the human cells in order to accelerate transition through the PS [21,40] but not to the mESCs. The activation of Wnt signaling and induction of PS formation requires external signals but is self-reinforcing after initiation [40].…”
Section: Resultsmentioning
confidence: 99%
“…Wnt3a is added to the human cells in order to accelerate transition through the PS [21,40] but not to the mESCs. The activation of Wnt signaling and induction of PS formation requires external signals but is self-reinforcing after initiation [40]. Wnt3a is coexpressed with Brachyury, which is a direct target of Wnt3a signaling [41] in the PS during gastrulation [42,43].…”
Section: Resultsmentioning
confidence: 99%